Factors affecting radial growth of Quercus ilex L. in a coppice stand in southern France - Cartan-Son, M.; Floret, C.; Galan, M. J. (Plant Ecology, 1992)
Quercus ilex woodlands in the south of France are characterized by low productivity. Several hypo- theses have been put forward to provide an explanation for this phenomenon: (i) senescence of coppice stumps; (ii)limited availability of water and nutrient resources; (iii)intershoot and inter-plant compe- tition. To test some of these hypotheses, growth response to rainfall distribution and nutrient supply (NPK), and the influence of edge effects after clear-cutting were studied in a 40-yr old stand. Curves of radial increment were compared with precipitation and umbrothermic patterns for the 6 years studied. Water availability apparently accounted for some inter-annual differences in growth. However, it was not mean annual rainfall, but rather rainfall occurring in late spring-summer (June, July) which played a large role in determining radial growth. Radial growth was also increased by nutrient supply. Its positive effect was strengthened by favourable rainfall in 1987. Edge-effects following a clear-cut were also found, both in the first year and in four succeeding years following the cut. This comprised in greater radial growth rate for all shoots, with reduced repression of smaller shoots by the larger ones. The effect decreased over a distance of 10 m with increasing distance from the cut field. This could be explained by increased availabiDLy of water, nutrient resources, and light.
Keywords: clear-cutting; edge effect; Mediterranean climate; nutrient supply; productivity